2010
DOI: 10.1007/s00044-010-9461-8
|View full text |Cite
|
Sign up to set email alerts
|

2,4,6-Trihydroxybenzaldehyde as a potent antidiabetic agent alleviates postprandial hyperglycemia in normal and diabetic rats

Abstract: Five distinct organic compounds with protected and unprotected phenolic hydroxyl groups were screened for their a-glucosidase inhibitory potential. Of these compounds, 2,4,6-trihydroxybenzaldehyde (THB) showed the strongest noncompetitive a-glucosidase inhibition (IC 50 = 4.60 lM) and the most powerful antioxidant activity (DPPH assay) (IC 50 = 71.4 lM) in vitro. In in vivo studies, THB significantly reduced blood glucose levels in normal and diabetic rats after glucose load compared to maltose load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…However, reports of inhibition of cycloartane-type triterpenes on α-glucosidase are limited, and there have been no reports about the effects of their structure–activity relationships on the strength of α-glucosidase inhibition. Antioxidants are substances that can prevent, stop, or reduce oxidative damage; therefore, they are able to protect the human body from several diseases, such diabetes and the complications associated with this disease [22]. The combination of α-glucosidase inhibitors and antioxidants was recently shown to be effective on treating diabetes mellitus and preventing its development [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, reports of inhibition of cycloartane-type triterpenes on α-glucosidase are limited, and there have been no reports about the effects of their structure–activity relationships on the strength of α-glucosidase inhibition. Antioxidants are substances that can prevent, stop, or reduce oxidative damage; therefore, they are able to protect the human body from several diseases, such diabetes and the complications associated with this disease [22]. The combination of α-glucosidase inhibitors and antioxidants was recently shown to be effective on treating diabetes mellitus and preventing its development [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…25 Additionally, were observed peaks were observed at the d 110-168 range, assigned to galloyl units. 26 The complete structure of the bioactive compound was determined by analysis of the HMBC spectrum, which showed cross peaks between the signals at d 7.01 (H-2´ and H-6´) and d 166.4 (C-7') as well as between the peaks at d 6.14 (H-1) and d 166.4 (C-7'). Finally, the comparison of NMR data with those described in the literature [25][26][27] (Table 1) allowed the identification of 1,2,3,4,6-penta-O-galloyl-b-D-glucose (PGG) Figure 1, whose occurrence has been described for the first time in the Plectranthus genus.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Pharmacologically, this substance showed diverse biological activities, such as antioxidant, 25 anticancer, 29 and inhibitory action against the invasion of mouse melanoma. 30 Additionally, an inhibitory effect of the a-glycosidase of PGG was described, suggested by the presence of galloyl substituents at the glucose unit 26 . Ethnopharmacological studies have revealed anti-parasitic activity of the Plectranthus species, especially an anti-leishmanial effect.…”
Section: Resultsmentioning
confidence: 99%
“…The production of ROS increases under diabetic conditions (Noh and Ha 2011;Ha et al 2008). Meanwhile, alphaglucosidase inhibitors helped control postprandial blood glucose levels in diabetic patients (Sancheti et al 2011;Gurudeeban et al 2012). It reduce the digestion and delay the absorption of carbohydrates, which relieved the postprandial increase in blood glucose levels (Cheng and Josse 2004).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Some reports suggested that decreasing the level of postprandial hyperglycemia is one of most effective therapeutic approaches in the early period of diabetes mellitus (Lee et al 2009;Ghadyale et al 2011;Van de Laar et al 2012). Other studies demonstrated that alpha-glucosidase inhibitors helped to control postprandial blood glucose levels in diabetic patients (Sancheti et al 2011;Gurudeeban et al 2012).…”
Section: Introductionmentioning
confidence: 99%